The Critical Study of Radio Azad Jamu and Kashmir Drama Chinaroun Kay Aansu - Ali, Abid; Altaf Hussain, Muhammad; Iqbal, Sadiq (sourcecoder, 2022)
In regions of Azad and occupied Kashmir, radio Muzaffarabad and its broadcasting enhanced Kashmir art and culture along with independent movement of Kashmir that was propagated to the whole world and played a role of silent soldiers for independence movement of Kashmir this is the reason, the broadcasting of radio dramas in Azad Kashmir earned historical, social, political, civilizational and literally identity in Kashmir.